Badania i rozwój jako element przedsiębiorczości w krajach europejskich - Gierańczyk, Wiesława (Przedsiębiorczość - Edukacja, 2010)
The article discusses the issue of innovation in economies of European states against the USA, Japan and China. It is based on the size of investment in the R&D sector in relation to the GDP (GERD/GDP) as well as the structure of these investments. In accordance with the research the EU27 spends much less on the R&D sector than its largest competitors. Besides, the EU is diversified in those terms. In 2006 the GERD/GDP index ranged from 3.74% in Sweden to 0.43% in Cyprus. Moreover, the EU also shows a different structure of the sources of capital invested in this sector that the other studied states. Generally, the lower inclination to investment into the R&D sector is visible within the sector of companies, which lies at the basis of efficiency of the innovation system.